ANALISIS DETERMINAN PRAKTIK TAX AVOIDANCE PADA PERUSAHAAN SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2019-2023 - Sibarani, Revalino Sahat Tua; Espa, Vitriyan; Haryono (AKUNTANSI DEWANTARA, 2024)
This research aims to analyze the effect of leverage, capital intensity, profitability, and institutional ownership on tax avoidance in the food and beverage subsector companies listed on the IDX during the period of 2019-2023. 17 companies were selected using purposive sampling technique, resulting in 85 observations for the analysis The analytical method employed is panel data regression using Eviews 10. The results show that partially leverage, capital intensity, and institutional ownership have no significant effect on tax avoidance. However, profitability has a negative and significant effect on tax avoidance. Simultaneously, leverage, capital intensity, profitability, and institutional ownership have a significant effect on tax avoidance. According to agency theory, principals and agents are prepared to accept high tax consequensces if the companies achieve high profitability. Additionally, tax practitioners should particularly monitor companies with low profitability, as tax avoidance tends to increase.